Implement Surveillance System using Raspberry PI and OpenCV - قبلان, هيا; علي اسماعيل, (Latakia University Journal -Engineering Sciences Series, 2023)
The Internet of Things has witnessed increasing growth in recent years, and it is the embodiment of smart services that resulted from the transformation of things into smart, connected things that are able to interact with their surroundings, and one of the most prominent realistic examples in this field is smart Surveillance applications, security has always been a source of great concern for homes, companies and institutions, The Internet of Things came loaded with innovative and smart solutions for buildings to achieve these goals, and more secure systems were achieved with cheaper costs and less energy use than using the old system such as closed-circuit television (CCTV). The same applies to facial recognition, where it has obtained a wide field of research and a great application in the field of the Internet of things. we built an effective and inexpensive smart home monitoring application using the Raspberry PI and Open CV, the application broadcasts real-time video (live video streaming) using the pi-camera connected to the Raspberry PI when motion is detected, then the frame is sent to the server using the python socket API to be processed by face detection using Haar cascade algorithm and face recognition using LBPH algorithm.